Турбулентная биоконвекция - Авраменко, А.А.; Басок, Б.И.; Кузнецов, А.В.; Тыринов, А.И. (Видавничий дім "Академперіодика" НАН України, 2008)
The problems concerning the processes of turbulent bioconvection are considered. These processes are typical of technologies of microbiological and other industries. On a basis of the renormalization group approach, the expressions for the turbulent diffusion constant are obtained.